Novel Combined Feeding Approach to Produce Quality Al6061 Composites for Heat Sinks - Asokan Manivannan; Rathinasabapathy Sasikumar; Khadar Shaik Dawood Abdul; Khan Mohammed Sadique (High Temperature Materials and Processes, 2019)
This elementary work aims to address agglomeration and non-uniform dispersion of reinforcement particles in stir casting using Al6061 alloy (AA 6061) as a matrix and Aluminium oxide (Al2O3) as reinforcement particles. A novel combined feeding method of Encapsulate feeding technique & Two Step Stir Casting was developed & attempted to produce good quality composites by varying weight fractions of Aluminium Oxide (0 to 5 wt.%). The wetting agent Mg (2 wt.%) added in all castings to ensure better binding between ceramics and matrix. The SEM photomicrograph ensures homogenous dispersion of reinforcement particles by combined feeding method. The thermal properties of produced good quality composites are enhanced with increase in Aluminium Oxide (Al2O3) from 0 to 5 wt.%.